Efficacy and safety of sofpironium in treatment of primary hyperhidrosis: a systematic review - Ramez M. Odat; Abdullah Yousef Aldalati; Bara M. Hammadeh; Ayham Mohammad Hussein; Muhammad Idrees; Hamza Marzouk; Sakhr Alshwayyat; Hamdah Hanifa (Journal of Dermatological Treatment)
Background Primary axillary hyperhidrosis has limited noninvasive and effective treatment, and we present the use of sofpironium bromide as a promising treatment option. We aimed to assess the efficacy and safety of sofpironium in patients with primary hyperhidrosis.Methods We systematically searched the databases for Studies that assessed sofpironium bromide in patients with primary axillary hyperhidrosis. Methodological quality was determined using the Cochrane Risk of Bias Assessment tool and Newcastle-Ottowa scale.Results Five studies were included (752 patients). They used 5% sofpironium, except for one study that used 5%, 10%, and 15% sofpironium. Studies have shown a significant difference in the incidence of patients with an HDSS score of 1 or 2 ranging from 53.9% to 86.7% and reported a greater reduction in the mean change in the DLQI score in the sofpironium group. They also noted a more significant reduction in the total gravimetric weight of sweat in the sofpironium group. A 1.5 point or greater improvement in HDSM-Ax score ranged from 48.2% to 69.1%. Serious adverse events were not observed in the intervention group.Conclusion Sofpironium gel provides notable improvements in symptom severity, sweat reduction, and quality of life, with mostly mild localized adverse events.Hyperhidrosis is relatively common, affecting 4.8% of the US population and negatively affects physical, social, and psychological well-being.Sofpironium bromide is recently approved by the FDA for the treatment of primary axillary hyperhidrosisSofpironium bromide showed promising results in terms of safety and efficacy for treating hyperhidrosisWe systematically assessed the use of sofpironium gel reported in five studies (752 patients)Sofpironium gel provides notable improvements in symptom severity, sweat reduction and quality of life, with mostly mild localized adverse events.